Visões sobre o rio Araguaia : imprensa goiana e imaginário no século XIX - Eliete Barbosa de Brito Silva; Leandro Mendes Rocha (Confins)
Water is essential to people's lives. Its symbolism is linked to the sacred, the mythical. Rivers are the conductors of this fluid. By extension, they have become the relevant space for the subjects. These, in their imagination conceive rivers as key elements for the production and maintenance of life forms. They are agents of fertilizing fields. They are the food sources, they are the roads. They are a potential. They are also builders of cities. These grow like mushrooms to use the river. This is what happened with Aruanã, city of Goiás on the banks of the river Araguaia. This river was the connecting route between the provinces of Goias and Grão-Pará. Road for the interiorization of the country. This article presents a reading of the Araguaia River by the press of the nineteenth century. We analyse the publications of magazines like "A Matutina Meyapontense (1830-1834)". Brazil of the nineteenth century was traversed by various scientific expeditions. These have entered the interior of the country and have given us a very rewarding reading of the places travelled. Among them, the space of the Rio Araguaia. Our objective was to disentangle the physical and social construction of the Rio Araguaia by the press, influenced by the vision of the travellers and the political interests of this century. Understand how the visions of the Rio Araguaia by these newspapers had repercussions and peopled the imagination and subsequent reports.